HUBUNGAN AKTIVITAS FISIK HARIAN DENGAN TINGKAT KEBUGARAN JASMANI SISWA SD - Brema Bangun; Tri Widia Astuti Tamba; Aditya Sitepu (STKIP Subang, 2026)
This study aims to determine the relationship between daily physical activity and the physical fitness levels of elementary school students. Physical activity is an important factor in children's growth because it contributes to bone health, muscle development, motor skills, physical fitness, and cognitive function. The WHO states that physical activity in children and adolescents plays a role in improving physical fitness, cardiometabolic health, bone health, mental health, and reducing body fat. This study used a quantitative approach with a correlational design. The sample consisted of 60 fourth and fifth grade elementary school students selected using a purposive sampling technique. The physical activity instrument used a daily physical activity questionnaire, while physical fitness was measured through a physical fitness test covering endurance, strength, agility, speed, and flexibility. Data were analyzed using a Pearson correlation test. The results showed a positive relationship between daily physical activity and students' physical fitness levels. This means that the higher a student's daily physical activity, the better their physical fitness level. This study concludes that the habit of daily physical activity needs to be improved through physical health education, active play, extracurricular sports activities, and reducing sedentary behavior.